REMOVAL OF HEAVY METALS USING CHLORELLA VULGARIS: A REVIEW - Fitri, Wiya Elsa; Putra, Adewirli; Febria, Fuji Astuti (LLDIKTI X Sumbar, Riau, Jambi, Kepri, 2024)
In this review, the researchers describe a natural process that can remove heavy metals from the environment. The use of Chlorella vulgaris has more potential than other bioremediation processes. Chlorella vulgaris has been recognized as a biomaterial capable of removal and could be a potential alternative method for the physicochemical absorption of heavy metals. The removal of heavy metals using Chlorella vulgaris on living cells can occur rapidly, independent of absorption of metabolism to the cell surface and intracellular absorption. Non-living cells have also successfully removed heavy metals from liquid waste. As one of the innovative removal technologies, it depends on algae's biosorption and bioaccumulation capabilities, which dominate the bioremediation process. This study shows that the composition of Chlorella vulgaris constituents, such as proteins, lipids, carbohydrates, pigments, vitamins, and minerals, which have various amino acid, hydroxyl, carboxyl, and sulfate functional groups, are the main factors in the absorption process of heavy metals in liquid waste, so they have the potential sustainability in its use as a bio adsorbent in the removal of heavy metals in liquid waste in the future.